Cigarette smoking and risk of intracranial aneurysms in middle-aged women. Issue 9 (28th July 2020) - Ogilvy, Christopher S; Gomez-Paz, Santiago; Kicielinski, Kimberly P; Salem, Mohamed M; Akamatsu, Yosuke; Waqas, Muhammad; Rai, Hamid Hussain; Catapano, Joshua S; Muram, Sandeep; Elghareeb, Mohammed; Siddiqui, Adnan H; Levy, Elad I; et al.
Abstract : Background and purpose: We previously reported a single-centre study demonstrating that smoking confers a six-fold increased risk for having an unruptured intracranial aneurysm (UIA) in women aged between 30 and 60 years and this risk was higher if the patient had chronic hypertension. There are no data with greater generalisability evaluating this association. We aimed to validate our previous findings in women from a multicentre study. Methods: A multicentre case-control study on women aged between 30 and 60 years, that had magnetic resonance angiography (MRA) during the period 2016–2018. Cases were those with an incidental UIA, and these were matched to controls based on age and ethnicity. A multivariable conditional logistic regression was conducted to evaluate smoking status and hypertension differences between cases and controls. Results: From 545 eligible patients, 113 aneurysm patients were matched to 113 controls. The most common reason for imaging was due to chronic headaches in 62.5% of cases and 44.3% of controls. A positive smoking history was encountered in 57.5% of cases and in 37.2% of controls. A multivariable analysis demonstrated a significant association between positive smoking history (OR 3.7,  95%CI 1.61 to 8.50), hypertension (OR 3.16,  95% CI 1.17 to 8.52) and both factors combined with a diagnosis of an incidental UIA (OR 6.9,  95% CI 2.49 to 19.24). Conclusions: Women aged between 30 and 60 years with a positive smoking history have a four-fold increased risk for having an UIA, and a seven-fold increased risk if they have underlying chronic hypertension. These findings indicate that women aged between 30 and 60 years with a positive smoking history might benefit from a screening recommendation.